An Anthropolinguistic Analysis of Cenning Rara as a Ritual Oral Tradition in Buginese Culture - Zulfiqri Saputra Samsul; Dian Rahmawati Arief (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study examines Cenning Rara, a sacred oral tradition in Buginese culture, through an anthropolinguistic perspective. Unlike narrative folklore, Cenning Rara functions as a ritual speech performance recited in bridal preparations and personal adornment contexts, where language is believed to possess spiritual efficacy. This research aims to analyze the linguistic structure, figurative expressions, and indexical meanings embedded in selected Cenning Rara texts. The data were analyzed using morphemic segmentation, parts-of-speech identification, literal and free translation comparison, and interpretation of figurative language based on Perrine’s classification. In addition, indexicality and symbolic functions were examined to understand how meaning operates within ritual performance. The findings reveal that Cenning Rara employs metaphor, hyperbole, symbolism, and celestial imagery to construct ideals of beauty, loyalty, and spiritual purity. Linguistically, reduplication, affixation, and rhythmic repetition reinforce its poetic and performative qualities. Indexically, the ritual speech points to social identity, gender ideology, moral values (siri’, lempu’, pesse), and spiritual mediation between the physical and metaphysical realms. The study demonstrates that Cenning Rara is not merely aesthetic language but a performative act that sustains cultural continuity and reinforces Bugis cosmology. This research contributes to anthropolinguistic studies by highlighting how ritual language functions as both cultural resource and social action in contemporary Bugis society.